How health knowledge that can influence patient outcome - Pereira, L.; Jerónimo, C. H.; Salgado, A.; Dias, Á.; Lopes da Costa, R.; Gonçalves, R. (International Journal of Medical Engineering and Informatics, 2024)
Since COVID-19 was declared a global pandemic, it has killed more than two million people worldwide. Some directly due to complications and symptoms of the virus others due to lack of resources to take care of all the patients affected by it. A proper triage can go a long way to an efficient resource allocation, which makes it extremely relevant to understand which factors can affect COVID-19 complications or mortality risk. With the analysis of survey data collect form front-line Portuguese doctors, it was possible to identify the main comorbidities and health issues that can influence patient outcome.